Cultura da figueira (Ficus carica L.) submetida a diferentes lâminas de irrigação por gotejamento - Trevisan, Patricia Verônica (2014)
The objective of this study was to evaluate the productivity fig tree (Ficus carica L) subjected to different drip irrigation levels. The fig tree is a species susceptible to drought, especially in the fruiting period. An experiment was conducted in the fruit-growing sector of the Polytechnic School of the Federal University of Santa Maria, RS. The plants were in the eighth year of production, and were evaluated from August 2012 to April 2013. The experimental design was randomized blocks with 5 treatments and 4 replications, considering two plants per unit experimental, totaling 40 plants arranged in spaced 2.5 x 2.0 m. The irrigation system used was located drip, in which treatments consisted of applying water slides, corresponding to replacement of 0, 50, 75, 100, and 125%, applied every 20 mm of maximum crop evapotranspiration (ETc) which was estimated by the equation Penmam Monteith. The variables analyzed were: fruit weight (g), fruit diameter (mm), fruit length (mm), number of fruits per plant, yield in t. ha-1 and ranked as the ripe fruit diameter (mm) and length (mm) of fruit. Evaluation results were submitted to analysis of variance (F test) and the differences between means were compared by Tukey test at 5% probability. The results of this study showed that the treatments had no answer for the fruit weight parameters (g), fruit diameter (mm), number of fruits per plant and yield (t. Ha-1), but the irrigation did not influence the length fruits (mm).